Statistics of aberrations in polycrystalline materials - Hernandez, J. A. (2007)
This thesis is concerned with the propagation of elastic waves in polycrystalline materials. In particular, in establishing a relationship between the statistical properties of the wavefield and the statistical properties of the material via a correlation function. Here the study of elastic waves has been restricted to surface acoustic waves (SAWs), mainly because they are readily accessible using an optical scanning acoustic microscope (OSAM)